Ke-'adalah-an Aisyah Perspektif Syiah dan Implikasinya Terhadap Hadis Nabi - Muhid; Imron, Moh Imron; Nurita, Andris (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
The Islamic Ummah has agreed that Aisha was one of the companions and wife of the Prophet. He is one of the seven most memorized hadiths. His enormous contribution to the development of Islam is proven by the more than two thousand hadiths he memorized. However, ironically, some Muslim minorities, especially the Shia school of thought, still doubt Aisyah's existence. Denying his existence so that it has implications for the history he conveys is unacceptable. It is these ideological differences that become academic anxiety, and it is necessary to conduct a study of Shia ideology in assessing friends, especially Aisyah. This was done to know the reasons and Shia foundations in assessing the existence of the companions of the Prophet. The methodology used in this study is a qualitative research methodology with the type of library research and data mining techniques with documentation. The results of this study conclude that Shia has its ideology in assessing the credibility of the companions of the Prophet. The basis used by Shia in building their ideology is the Qur'an and Hadith, with various interpretations. Thus resulting in the conclusion that all of the Prophet's companions after the Prophet died were apostates except for a few who were still saved in their religion. Included in the apostate category is Aisyah. He is a disabled person, and his transmission cannot be accepted.